Sharia-Based Accounting Information System in the Development of Integrated Cooperatives - Evi Maulida Yanti; Agussalim M; Cut Yusnidar; Syamsul Akmar (International Journal of Economics Development Research (IJEDR), 2023)
This research is quantitative research that focuses on Sharia Cooperatives in Aceh Province. Data was collected using primary data on 136 sharia cooperatives. Each sharia cooperative office selected 3 people as correspondents, out of a total of only 300 correspondents who returned complete questionnaires. The results of the research show that the accounting information system influences cooperative performance, cooperative growth influences cooperative performance, accounting information systems influence Islamic social capital, cooperative growth influences Islamic social capital, Islamic social capital influences cooperative performance, Islamic social capital mediates the influence of the system. Accounting information on cooperative performance and Islamic social capital mediate the influence of cooperative growth on cooperative performance. It can be concluded that in building cooperative performance, a good accounting information system and adequate social capital are needed, apart from that it functions to ensure the accuracy of the accounting information system and social capital that is run